Biological parameters of fish stock estimation in Cirata Reservoir (West Java, Indonesia): A comparative analysis of bio-economic models - ZUZY ANNA; ASEP AGUS HANDAKA SURYANA; INE MAULINA; ACHMAD RIZAL; PURNA HINDAYANI (Society for Indonesian Biodiversity, 2017)
Anna Z, Handaka AA, Maulina I, Rizal A, Hindayani P. 2017. Biological parameters of fish stock estimation in Cirata Reservoir (West Java, Indonesia): A comparative analysis of bio-economic models. Biodiversitas 18: 1468-1474. Fish resources in reservoirs such as Cirata have a strategic value, especially for the surrounding community in terms of fulfilling the need for nutricious food, subsistence, and economic purposes. Unfortunately, until now there has been no serious attention from the government to develop and manage fish resources in these waters. From time series data it can be seen that there is a decrease in fish production, which is an indication of a decrease of fish stock, which has a negative impact on the wellfare of surrounding commmunity, as well as the sustainability of fish resources and their ecosystems. To meet the food safety and economic needs of the community, a healthy and sustainable fish resource is a must, characterized by sustainable inputs and outputs, so that the stock of fish resources will be maintained. In order to fulfill this need, a basic understanding of the biological and economic conditions of the dynamics of fish resources in these waters as a basis for sustainable management is needed. Research was conducted to calculate the biological parameters of fish resources through Fox, CYP, Walters Hilborn and Schnute algorithms, using quarterly catch and effort data from 2011 to 2015, collected from secondary and cross checking data. Furthermore, using price and cost data series, adjusted by consumer price index, the variable of input, output and economic rent of sustainable, optimal and open access management regimes were analyzed. The results of the study indicate that the most statistically appropriate model for estimating biological parameters in Cirata are the Fox and CYP models, and fisheries management using the optimal regime provides the most efficient results, where fewer inputs will result in the maximum profit. The research suggests the need for immediate enforcement of management rules based on sustainable management regimes through input or output restrictions on capture fisheries in Cirata Reservoirs.